Survei Efektivitas Penggunaan Metode Penugasan dalam Pembelajaran Penjas (PJOK) Selama Pembelajaran Jarak Jauh di Madrasah Aliyah Negeri 1 Kota Bekasi (MAN) - Syaifullah Alabba; Rekha Ratri Julianti; Setio Nugroho (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the effectiveness of using the assignment method in physical education learning, which was measured based on five factors, quality of learning, level of learning suitability, incentives, use of time and distance learning conditions. The sample used in this study were students of MAN 1 Bekasi City with a total of 75 people. The data collection technique used in this study is a quantitative descriptive technique. The method used is a survey, data collection techniques using a questionnaire in the form of a Likert scale. The results showed that the effectiveness of using the assignment method in physical education learning during distance learning was in the "very good" category with a percentage of 7% (5 students), "good" 21% (16 students), "good enough" 39% (29 students). ),“low” 28% (21 students), “very low” 5% (4 students). Based on these results, it can be concluded that the use of the assignment method in physical education learning during distance learning is in the quite effective.